2022
DOI: 10.3390/medicina58111676
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic versus Systolic Left Ventricular Dysfunction as Independent Predictors for Unfavorable Postoperative Evolution in Patients with Aortic Regurgitation Undergoing Aortic Valve Replacement

Abstract: Background and Objectives: Chronic severe aortic valve disease is associated with important changes in left ventricle (LV) performance associated with eccentric or concentric LV hypertrophy. We aimed to assess the immediate prognostic implications of the type of the LV diastolic filling pattern (LVDFP) compared with LV systolic performance in patients with severe aortic regurgitation (AR) undergoing aortic valve replacement (AVR) and to define the independent echographic predictors for the immediate and long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 25 publications
6
14
0
Order By: Relevance
“…As in our study, other researchers have shown that the early postoperative evolution of patients with AR is usually more unfavorable [ 7 , 8 ]. Moreover, at 1 year postoperatively, the NYHA class and self-reported quality of life in our study groups was found better after the AVR for AS compared to AR, as was reported in other previous studies [ 22 ].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…As in our study, other researchers have shown that the early postoperative evolution of patients with AR is usually more unfavorable [ 7 , 8 ]. Moreover, at 1 year postoperatively, the NYHA class and self-reported quality of life in our study groups was found better after the AVR for AS compared to AR, as was reported in other previous studies [ 22 ].…”
Section: Discussionsupporting
confidence: 79%
“…Most studies have shown that, in the majority of patients with AS, LV diastolic function returned to normal after the valve replacement [ 24 , 25 , 26 ]. In contrast, in AR, diastolic dysfunction with abnormal filling is maintained in a significant percentage of patients after surgical correction, being normalized late after surgery [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations